Iluminação integrativa: análise de sala de terapia renal substitutiva - Freitas, Juliana Pimentel (2023)
Lighting in the built environment has an influence on human health and wellbeing, including psychological and physiological aspects. In this sense, in environments such as dialysis rooms, lighting can have positive effects when considering the patient's length of stay in this space, as well as in relation to the stress and anxiety associated with therapy. Thus, Integrative Lighting is relevant for the integrated analysis of the visual and non-visual effects of light. Considering the specificity of the theme, the main objective of this research is to analyze the effects of Integrative Lighting and its suitability in hospital environments, specifically dialysis rooms. For this, based on the literature, questions related to the environmental characteristics considered essential in the promotion of Integrative Lighting were listed and grouped, here called “categories”: illuminance, spectrum and color temperature, and view from the outside. Thus, the methodology comprised two phases. The first phase refers to the elaboration of a checklist that covers the categories, the evaluation parameters and the requirements to be met. The second phase, in turn, consists of presenting the procedures for analyzing the checklist items, with the subsequent object of application and analysis being the dialysis room of the Renal Replacement Therapy Unit in São Mateus-ES. In conclusion, it is observed that for "illuminance", the parameters to be analyzed include the "visual system" (according to normative guidelines for performance) and the "non-visual system" (according to circadian metrics). In this sense, it is inferred that environmental conditions in a healthcare space must reconcile satisfactory results that concern safety, visual performance, and maintenance of the circadian rhythm. For "spectrum and color temperature", the parameter "adequacy and control" was observed as an intention to reproduce, in the indoor environment, the benefits provided by the dynamism of natural light. Thus, the relevance of access to natural light in the built environment was observed, with its absence presupposing the existence of a dynamic system of artificial lighting. With regard to the "exterior view", the parameters "content" and "access" were established for the analysis of the connection established between the interior and exterior through the opening. Thus, it is possible to conclude that both the content of the view and access to it are necessary to ensure the occupant's well-being through the fulfillment of requirements related to the characteristics of the surroundings, the opening material, and its elements that qualify the occupied interior space. The fact that many of the listed requirements were not met by the characteristics of the dialysis room of the UTRS allowed us to understand the need to rethink the architectural design for such spaces, whose occupation is so significant and prolonged.